Transformasi Ekonomi Pertanian Lokal Melalui Pendekatan Ekonomi Islam di Kutalimbaru Pasar X - Muhammad Abdul Arip; Dicky Pratama; Raissa Amanda Putri (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
The transformation of the local agricultural economy in Kutalimbaru Pasar X faces challenges due to the low added value of banana products, caused by a simple distribution pattern. Farmers sell their harvest in its raw form to middlemen without any processing or collective management. As a result, the bargaining power of farmers is weak, and profit distribution is uneven. This study aims to analyze the implementation of the Islamic economic approach in the transformation of the local agricultural economy. The method used is descriptive qualitative, involving field observations, interviews with farmers, and literature review. The research findings show that strengthening farmer institutions, implementing transparent pricing mechanisms, and post-harvest processing can increase the added value of products and improve profit distribution. The application of Islamic economic principles, such as justice, cooperation, and accountability, can establish a fairer and more sustainable village economic system. This economic transformation also impacts the increase in farmers' income and strengthens the economic resilience of the community-based society. By integrating Islamic economic principles, it is hoped that the local agricultural sector can develop more productively and provide equitable benefits for all parties involved in the production and distribution processes.